Hasard-Schicksale: Der literarische Zufall und das Glücksspiel im 19. Jahrhundert - Thede, Sebastian (transcript, 2017)
Chance or fate? Key novels and short stories of the long 19th century illuminate the literary potential of an unsolvable dilemma.